Significance of shallow core transects for reef models and sea‐level curves, Heron Reef, Great Barrier Reef. Issue 6 (13th May 2016) - Webb, Gregory E.; Nothdurft, Luke D.; Zhao, Jian‐Xin; Opdyke, Bradley; Price, Gilbert
Abstract: A sequence of shallow reef cores from Heron Reef, Great Barrier Reef, provides new insights into Holocene reef growth models. Isochron analysis of a leeward core transect suggests that the north‐western end of Heron Reef reached current sea‐level by ca 6·5 kyrbp and then prograded leeward at a rate of ca 19·6 m/kyr between 5·1 kyr and 4·1 kyrbp (pre‐1950) to the present reef margin. A single short core on the opposing margin of the reef is consistent with greater and more recent progradation there. Further to the east, one windward core reached modern sea‐level by ca 6·3 kyrbp, suggesting near 'keep‐up' behaviour at that location, but the opposing leeward margin behind the lagoon reached sea‐level much more recently. Hence, Heron Reef exhibited significantly different reef growth behaviour on different parts of the same margin. Mean reef accretion rates calculated from within 20 m of one another in the leeward core transect varied between ca 2·9 m and 4·7 m/kyr depending on relative position in the prograding wedge. These cores serve as a warning regarding the use of isolated cores to inform reef growth rates because apparent aggradation at any given location on a reef varies depending on its location relative to a prograding margin. Only transects of closely spaced cores can document reef behaviour adequately so as to inform reef growth models and sea‐level curves. The cores also emphasize potential problems in U‐series dates for corals within a shallow ( ca 1·5 m) zone beneath the reef flat. Apparent age inversions restricted to that active diagenetic zone may reflect remobilization and concentration of Th in irregularly distributed microbialites or biofilms that were missed during sample vetting. Importantly, the Th‐containing contaminant causes ages to appear too old, rather than too young, as would be expected from younger cement.